America's secret power: the CIA in a democratic society - Johnson, Loch K. (Oxford Univ. Pr., 1989)
Loch K. Johnson: America's Secret Power. The CIA in a Democratic Society. Oxford University Press, New York, Oxford 1989. 344 Seiten, 24,95 Dollar